2006
DOI: 10.1159/000098142
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Anemia Associated with Micronutrient Deficiencies Other than Iron in a Probabilistic Sample of Mexican Children

Abstract: Background: This investigation aims to explore the association among anemia and vitamins A, C, and folate deficiencies in a probabilistic sample of Mexican children. Methods: Data on hemoglobin, serum vitamins A and C and folate concentrations and percent transferrin saturation (PTS) in children 0.5–11 years (n = 1,770) were extracted from the database of the probabilistic Mexican National Nutrition Survey 1999 (NNS-99). Results: Overall, 16.6% of children were anemic. Iron deficiency children with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
3
22
0
2
Order By: Relevance
“…fortification, 14% of children had low erythrocyte folate concentrations and anemic children had significantly lower folate concentrations compared with non-anemic children (Villalpando et al, 2006). The mechanisms to explain an inverse relation between folate and hemoglobin concentrations in the absence of folate deficiency, particularly in subjects with inadequate vitamin B12 status, are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fortification, 14% of children had low erythrocyte folate concentrations and anemic children had significantly lower folate concentrations compared with non-anemic children (Villalpando et al, 2006). The mechanisms to explain an inverse relation between folate and hemoglobin concentrations in the absence of folate deficiency, particularly in subjects with inadequate vitamin B12 status, are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of anemia include poor school performance, reduced work capacity, increased susceptibility to infections, and stunted growth (Stoltzfus, 2001). While iron deficiency is the cause of approximately one-half of all cases of anemia (Zimmermann and Hurrell, 2007), deficiencies of other micronutrients, including folate, vitamin B12, and vitamin A, have also been identified as causes of low hemoglobin concentrations and anemia (Majia et al, 1977;Villalpando et al, 2006;Jones et al, 2007) through diverse mechanisms. Folate is a carbon donor for purine and pyrimidine synthesis, which are needed for the rapidly developing erythroid cells (Scott, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted with children in countries other than Brazil exhibited results similar to those presented in this article, with low serum retinol and folic acid levels being observed among children with anemia. 11,12 Research conducted in Northeast Brazil with pregnant women In Brazil, a recent nationwide study showed low frequency of sickle cell anemia in the population studied. 3 It is also noteworthy that microcytosis is not present in sickle cell anemia, except in cases of co-inheritance of thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (LAYRISSe et al, 1997;GARCíA-CASAL, 1998;GuNNARSSoN;ThoRSdoTTIR;PALSSoN, 2007;VILLALPANdo et al, 2006;zIMeRMANN, 2006) have observed that during the digestive process, iron and vitamin A form a new product or complex that keeps soluble iron at ph 6.0, hindering the inhibitory action of some anti-nutritional in the absorption of nonheme iron. β-carotene is more efficient than vitamin A to form a complex with iron because of its high stability during storage, handling and ph changes.…”
Section: Introductionmentioning
confidence: 99%